Hydride-based antiperovskites with soft anionic sublattices as fast alkali ionic conductors - Shenghan Gao; Thibault Broux; Susumu Fujii; Cédric Tassel; Kentaro Yamamoto; Yao Xiao; Itaru Oikawa; Hitoshi Takamura; Hiroki Ubukata; Yuki Watanabe; Kotaro Fujii; Masatomo Yashima; et al. (Nature Communications, 2021)
Oxide-based lithium/sodium-rich antiperovskites are regarded as promising solid electrolytes. Here, authors report a series of antiperovskites with a soft lattice containing hydride (H–) and chalcogenide (S2–, Se2–, Te2–) anions, enabling the fast Li+ /Na+ transport assisted by rotational phonon modes.